+0  
 
0
107
1
avatar

 The equation :        x-(1-x) √ 3=-5                                       

 Feb 8, 2021
 #1
avatar+11656 
+1

Solve this first-degree equation in one unknown, while writing all stages of the calculation

The equation : x-(1-x) √ 3=-5

 

Hello Guest!

 

\(x-(1-x) \sqrt{ 3}=-5\)       | multiply √3

\(x-(\sqrt{3}-x\sqrt{3})=-5\)   | (√3-x√3) multiply (-1)

\(x-\sqrt{3}+x\sqrt{3}=-5\)       | + √3

\(x+x\sqrt{3}=-5+\sqrt{3}\)       | x in front of the bracket

\(x(1+\sqrt{3})=-5+\sqrt{3}\)    | divide by the bracket

\(x=\frac{-5+\sqrt{3}}{1+\sqrt{3}}\cdot\frac{1-\sqrt{3}}{1-\sqrt{3}}\)            | multiply \(\frac{1-\sqrt{3}}{1-\sqrt{3}}\)

\(x=\frac{-5+5 \sqrt{3}+\sqrt{3}-3}{1-3}\)             | add

\(x= \frac{-8+6\sqrt{3}}{-2}\)                       | divide -2

\(x=4-3\sqrt{3}\)

laugh  !

 Feb 8, 2021

23 Online Users

avatar
avatar
avatar
avatar